2004
DOI: 10.1104/pp.104.038711
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Wall Deposition and Cell Elongation in Dark-Grown Hypocotyl Cells in Arabidopsis

Abstract: A central problem in plant biology is how cell expansion is coordinated with wall synthesis. We have studied growth and wall deposition in epidermal cells of dark-grown Arabidopsis hypocotyls. Cells elongated in a biphasic pattern, slowly first and rapidly thereafter. The growth acceleration was initiated at the hypocotyl base and propagated acropetally. Using transmission and scanning electron microscopy, we analyzed walls in slowly and rapidly growing cells in 4-d-old dark-grown seedlings. We observed thick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
148
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 37 publications
25
148
0
Order By: Relevance
“…The growing stem cells apparently coordinate growth with these cellular processes more closely than do Arabidopsis hypocotyls (Refrégier et al, 2004), whose cell walls thinned during elongation, or pea (Pisum sativum) epicotyls (Cosgrove and Cleland, 1983), whose cell osmotic pressure declined slightly along the elongation zone. The last two examples notwithstanding, plant cell growth is generally well coordinated with the production of cellular materials needed for mechanical stability, and the Arabidopsis inflorescence is a fine example of such coordination.…”
Section: Discussionmentioning
confidence: 99%
“…The growing stem cells apparently coordinate growth with these cellular processes more closely than do Arabidopsis hypocotyls (Refrégier et al, 2004), whose cell walls thinned during elongation, or pea (Pisum sativum) epicotyls (Cosgrove and Cleland, 1983), whose cell osmotic pressure declined slightly along the elongation zone. The last two examples notwithstanding, plant cell growth is generally well coordinated with the production of cellular materials needed for mechanical stability, and the Arabidopsis inflorescence is a fine example of such coordination.…”
Section: Discussionmentioning
confidence: 99%
“…sis was observed in pom1-21 mutant seedlings compared to the wild type (Mouille et al, 2003), (2) incomplete cell walls were observed in elp1 inflorescence stems (Zhong et al, 2002), and (3) AtCTL1 expression is highly coordinated with cellulose synthesis in primary walls, based on the expression patterns of cellulose synthases CESA1, CESA3, and CESA6 (Persson et al, 2005). Interestingly, mutations in CESA3 and CESA6 but also in KORRIGAN1 (KOR1)/RADIALLY SWOLLEN2, encoding a membrane-bound endo-1,4-b-D-glucanase, lead to similar reductions of PR growth and, to some extent, radial swelling as described in the arm mutant (Hauser et al, 1995;Fagard et al, 2000;Desprez et al, 2002;CanoDelgado et al, 2003;Refregier et al, 2004;Hématy et al, 2007). Therefore, we tested the effect of nitrate availability in the growth medium on the CESA3 (eli1-1), CESA6 (prc1-1), and KOR1 (kor1-1) mutant phenotypes (Fig.…”
Section: The Phenotype Of Cellulose Biosynthesis Mutants Is Conditionmentioning
confidence: 99%
“…Microtubules have been shown to guide the movements of cellulose synthesizing enzymes along the plasma membrane of Arabidopsis hypocotyl cells (Paredez et al, 2006) and so the fact that microtubule bundles undergo rotary movements themselves is likely to be fundamentally important for the organization of cellulose microfibrils in the cell wall (Giddings and Staehelin, 1991). Rotation might explain the helicoidal wall structure of hypocotyl (Refré gier et al, 2004) and stem (Hejnowicz, 2005) epidermal cells, in which cellulose microfibrils are arranged in layers that progressively change angle like the steps of a spiral staircase. Microtubule rotation may not, however, be a feature of other cells, such as elongating root cells, in which microtubules are organized in transverse alignments (Sugimoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%